2021
DOI: 10.1002/jwmg.22108
|View full text |Cite
|
Sign up to set email alerts
|

Brown Treesnake Mortality After Aerial Application of Toxic Baits

Abstract: Quantitative evaluation of control tools for managing invasive species is necessary to assess overall effectiveness and individual variation in treatment susceptibility. Invasive brown treesnakes (Boiga irregularis) on Guam have caused severe ecological and economic effects, pose a risk of accidental introduction to other islands, and are the greatest impediment to the reestablishment of extirpated native fauna. An aerial delivery system for rodent‐based toxic baits can reduce brown treesnake abundance and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For example, likely due to the ease of application and the scale at which ADS could be applied, the greatest per control day removal of snakes was by use of this tool. However, snakes in larger size classes have lower susceptibilities to acetaminophen intoxication and a reduced probability of mortality (Goetz et al., 2021; Siers et al., 2021), whereas carrion was apparently less attractive to snakes in good condition. The addition of live avian lures to the control programme was critical for removing good‐condition individuals and achieving extant avian responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, likely due to the ease of application and the scale at which ADS could be applied, the greatest per control day removal of snakes was by use of this tool. However, snakes in larger size classes have lower susceptibilities to acetaminophen intoxication and a reduced probability of mortality (Goetz et al., 2021; Siers et al., 2021), whereas carrion was apparently less attractive to snakes in good condition. The addition of live avian lures to the control programme was critical for removing good‐condition individuals and achieving extant avian responses.…”
Section: Discussionmentioning
confidence: 99%
“…Various removal methods targeting Trioceros jacksonii (Boulenger) (Jackson's Chameleon) in Hawaii have also been largely ineffective for similar reasons (Van Kleeck and Holland 2018). In both cases, the use of acetaminophen has been proposed as a potential solution (Goetz et al 2021, Van Kleeck and Holland 2018), which has also been tested as a potential method to remove Nile Monitors and Burmese Python in Florida (Mauldin and Savarie 2010). However, like concerns with other methods, the impacts of acetaminophen to non-target species are a major concern, especially in urban areas such as those inhabited by the Nile Monitor where non-target mortalities of pets could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Determining a proper removal method is a common obstacle to efforts to eradicate herpetofauna. For example, efforts to control Boiga irregularis (Bechstein) (Brown Tree Snake) in Guam have been limited by the labor demands and lack of large-scale application of most removal methods (Goetz et al 2021). Various removal methods targeting Trioceros jacksonii (Boulenger) (Jackson's Chameleon) in Hawaii have also been largely ineffective for similar reasons (Van Kleeck and Holland 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, bait attractiveness or palatability may be affected by size‐dependent attraction to dead neonatal mice, with larger snakes showing less interest (Savidge 1988, Shivik and Clark 1999). Prior studies of ADS‐treated populations suggested an accumulation of the largest snakes and the smallest snakes may occur after treatment and that large snakes may have lower risk of mortality (Nafus et al 2020, Goetz et al 2021), supporting reduced efficacy of small mouse‐based toxicants in removing those demographics. Although large snakes do consume and die from the baits, they may have increased survival rates relative to smaller size classes interested in endothermic prey (Siers et al 2021).…”
Section: Discussionmentioning
confidence: 99%